2019
DOI: 10.1253/circj.cj-19-0467
|View full text |Cite|
|
Sign up to set email alerts
|

Influence of Preadmission Frailty on Short- and Mid-Term Prognoses in Octogenarians With ST-Elevation Myocardial Infarction

Abstract: STEMI receiving PCI has not been evaluated sufficiently with regard to overall mortality and non-home discharge. The aim of this study was to evaluate the association of CFS with these clinical outcomes of octogenarian patients with STEMI. Methods Study Design and Population We screened the Nagoya multicenter registry for the data of consecutive patients with STEMI who underwent primary PCI between January 2014 and December 2016 (n=1,301). The registry is an ongoing, retrospective, multicenter registry of coro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
30
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 37 publications
2
30
1
Order By: Relevance
“…Both anemia and a low BMI have been identified as surrogate markers of frailty ( 29 , 31 ) in the elderly. Therefore, our findings may highlight the impact of frailty on the mid-term mortality, especially non-cardiac death, as previously reported by us ( 32 ).…”
Section: Discussionsupporting
confidence: 88%
“…Both anemia and a low BMI have been identified as surrogate markers of frailty ( 29 , 31 ) in the elderly. Therefore, our findings may highlight the impact of frailty on the mid-term mortality, especially non-cardiac death, as previously reported by us ( 32 ).…”
Section: Discussionsupporting
confidence: 88%
“…The mean ages of the included patients varied between 62 and 85 years, with proportions of males varying from 46 to 75%. Multiple tools were used for the evaluation of frailty among the included studies, including the Fried Frailty Criteria ( 15 , 17 ), the Canadian Study of Health and Aging Clinical Frailty Scale ( 16 , 22 ), validated frailty phenotype criteria ( 23 ), FRAIL scale ( 18 ), Claims-based Frailty Index ( 19 ), Safety Management Programme Score ( 20 ), Hospital Frailty Risk Score ( 24 ), and modified KATZ index ( 21 ). A total of 16,183 patients were considered with frailty at baseline.…”
Section: Resultsmentioning
confidence: 99%
“…However, the association between frailty and the prognosis of patients after PCI remains unclear (14). Most studies showed that frailty is independently associated with higher risk of mortality and adverse events after PCI (15)(16)(17)(18)(19)(20)(21)(22), while some did not (23,24). Accordingly, a previous meta-analysis included eight cohort studies and showed that frailty was associated with a higher risk of death for patients after PCI (25).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, it emphasized other conditions such as peripheral arterial disease and heart failure, which would make these subjects more likely to be frail, while in an inverse association analysis frailty would not precede the development of CVD 22 . In addition to the above, as it represents a greater risk for longlived old people in events related to AMI, studies suggest the assessment of frailty as a prognostic factor in the treatment of this population 23 .…”
Section: Discussionmentioning
confidence: 99%